Buffered 2% articaine in buccal infiltration of mandibular molars: a randomized triple-blind clinical trial - Sandro Alexander Lévano LOAYZA; Thomas BARBIN; Victor Augusto Benedicto dos SANTOS; Francisco Carlos GROPPO; Klinger de Souza AMORIM; Daniel Felipe Fernandes PAIVA; Sidney Raimundo FIGUEROBA (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This crossover study aimed to compare the anesthetic effects of buffered 2% articaine with 1:200,000 epinephrine with that of non-buffered 4% articaine with 1:200,000 epinephrine. Forty-seven volunteers were administered two doses of anesthesia in the buccal region of the second mandibular molars in two sessions using 1.8 mL of different local anesthetic solutions. The onset time and duration of pulp anesthesia, soft tissue pressure pain threshold, and the score of pain on puncture and burning during injection were evaluated. The operator, volunteers, and statistician were blinded. There were no significant differences in the parameters: onset of soft tissue anesthesia (p = 0.80), duration of soft tissue anesthesia (p = 0.10), onset of pulpal anesthesia in the second (p = 0.28) and first molars (p = 0.45), duration of pulp anesthesia of the second (p = 0.60) and first molars (p = 0.30), pain during puncture (p = 0.82) and injection (p = 0.80). No significant adverse events were observed. Buffered 2% articaine with 1:200,000 epinephrine did not differ from non-buffered 4% articaine with 1:200,000 epinephrine considering anesthetic success, safety, onset, duration of anesthesia, and pain on injection.